Sasak Islam in the Merariq Tradition in Central Lombok, Tumpak Village - Saidun; Encung (LECTURES: Journal of Islamic and Education Studies, 2023)
Regarding religion and culture on the island of Lombok, there are several traditions or cultures that are mixed with religion, one of which is the merariq tradition. However, in this Merariq tradition we will find two discussions, namely religion and culture which have different dimensions but are united or practiced simultaneously in one scope, namely in the traditional marriage tradition of the Sasak tribe. The problems raised in this study are divided into two aspects, how are the relations of Islamic culture in the Merariq tradition and how the efforts of the village community stack up in preserving the Merariq tradition. To find out more about this research, the researchers used an anthropological approach with a descriptive qualitative type with data collection techniques used in the form of observation techniques, interviews, and documentation. The results showed that the relationship between Islam and culture in the Merariq tradition is acculturative and contains Islamic elements, namely: Islamic elements in this tradition are from the two parties, religious weddings, the bride and groom, marriage guardians, witnesses, the marriage contract religion and custom, and dowry. The customary elements in this tradition are theft, banishment of a woman who is of a high caste if she marries a caste below her, ascending, the traditional version of the tradition itself. The forms of conservation of the merariq tradition from this research are: the merariq tradition symbolizes virility, raises the self-esteem of parents if the marriage is carried out by means of merariq rather than having to ask normally, eliminates caste (degrees). The results showed that the relationship between Islam and culture in the Merariq tradition is acculturative and contains Islamic elements, namely: Islamic elements in this tradition are from the two parties, religious weddings, the bride and groom, marriage guardians, witnesses, the marriage contract religion and custom, and dowry. The customary elements in this tradition are theft, banishment of a woman who is of a high caste if she marries a caste below her, ascending, the traditional version of the tradition itself. The forms of conservation of the merariq tradition from this research are: the merariq tradition symbolizes virility, raises the self-esteem of parents if the marriage is carried out by means of merariq rather than having to ask normally, eliminates caste (degrees). The results showed that the relationship between Islam and culture in the Merariq tradition is acculturative and contains Islamic elements, namely: Islamic elements in this tradition are from the two parties, religious weddings, the bride and groom, marriage guardians, witnesses, the marriage contract religion and custom, and dowry. The customary elements in this tradition are theft, banishment of a woman who is of a high caste if she marries a caste below her, ascending, the traditional version of the tradition itself. The forms of conservation of the merariq tradition from this research are: the merariq tradition symbolizes virility, raises the self-esteem of parents if the marriage is carried out by means of merariq rather than having to ask normally, eliminates caste (degrees).